PENGARUH DANA PERIMBANGAN BELANJA MODAL DAN FISCAL STRESS TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH DI KABUPATEN/KOTA PROVINSI SUMATERA UTARA - Padang, Novi Natalia; Padang, Wendi Suprapto (Jurnal Riset Akuntansi & Keuangan, 2024)
The purpose of this study was to determine and analyze the effect of balancing fund, capital expenditures and fiscal stress on the financial performance of local governments in the districts/cities of North Sumatra Province. The population for this study is the districts/cities of North Sumatra Province, consisting of 33 districts/cities with the observation years 2014 to 2021. The type of sample uses a saturated sample where the population is the sample. The data is processed using the panel data regression statistical test method. The results of this study prove that balancing funds, fiscal stress have a positive and significant effect on the financial performance of local governments in the districts/cities of North Sumatra Province. Meanwhile, capital expenditure has no effect on the financial performance of local governments in the districts/cities of North Sumatra Province.